Transparent powder coating composition and preparation method thereof
By introducing hydroxysilane monomer and polycarbonate diol into the GMA acrylic resin system of transparent powder coating, modifying the acrylic resin and cross-linking, the problem of poor scratch resistance of existing transparent powder coatings is solved, and a transparent powder coating composition with high hardness, wear resistance and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202510238571.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-03-03
AI Technical Summary
Existing transparent powder coatings have poor scratch resistance and are prone to damage when in contact with solid objects. Commonly used improved wax anti-scratch agents will affect the transparency of the coating.
The hydroxysilane monomer is introduced into the GMA acrylic resin system of transparent powder coating for modification. The silane segments float up when the coating is cured, giving the coating smoothness and scratch resistance. The hardness and wear resistance of the coating are improved by cross-linking of acrylic resin and the addition of polycarbonate diol.
It significantly improves the scratch resistance, boiling resistance and corrosion resistance of transparent powder coatings, avoiding the problems of reduced coating scratches and protective effects, while maintaining the transparency of the coating.
Smart Images

Figure CN119708944A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder coatings, and in particular to a transparent powder coating composition and a preparation method thereof. Background Art
[0002] Powder coating is a solid coating composition applied to a substrate in the form of a free-flowing powder by an electrostatic process. It provides colorful exterior decoration for building materials, home appliances, furniture and industrial metal products. For transparent powder coating systems, the most commonly used is GMA acrylic resin transparent powder coating. The advantages of this type of powder system are good transparency and weather resistance, but the coating has poor scratch resistance and is easily damaged when in contact with solid objects. The surface coating will be scratched due to impact and friction, affecting the surface appearance. Moreover, as the number of scratches on the coating increases, the protective effect of the coating will be reduced, causing the substrate to be corroded. The current method commonly used to improve the scratch resistance of the coating is to add an improved wax anti-scratch agent to the powder coating system, but the addition of such an anti-scratch agent alone will affect the transparency of the cured coating and cannot meet the use requirements.
[0003] To this end, a transparent powder coating composition and a preparation method are provided. Summary of the invention
[0004] The object of the present invention is to provide a transparent powder coating composition and a preparation method thereof. A hydroxyl silane monomer is introduced into the GMA acrylic resin system of the transparent powder coating for modification. When the coating is cured, the floating of the silane chain segment gives the coating smoothness and scratch resistance, and does not affect the transparency of the coating. The hydroxyl and epoxy functional groups in the acrylic resin are respectively cross-linked with a carboxyl curing agent and an isocyanate curing agent to increase the curing density and improve the hardness of the coating. Finally, polycarbonate diol is added to the modified acrylic resin adhesive or in the mixing process of the powder coating composition to assist in improving the hardness, wear resistance and boiling adhesion of the coating. The scratch resistance, boiling adhesion and corrosion resistance of the powder coating composition obtained in combination are greatly improved to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a transparent powder coating composition, comprising the following mass components, including 50wt%-80wt% of a hydroxysilane-modified GMA acrylic resin component, 15wt%-45wt% of a curing agent component, 1%-3% of a polycarbonate diol component, 0.1wt%-1.0wt% of a deaerator component, and 0.1wt%-2wt% of a leveling agent component.
[0006] Preferably, the molecular weight of the polycarbonate diol is between 1000 and 2000, and it is added during the synthesis of the hydroxysilane-modified GMA acrylic resin and during the premixing of the powder coating composition.
[0007] Preferably, the curing agent component is a compound that undergoes a cross-linking reaction with the hydroxysilane-modified GMA acrylic resin component, including acid and anhydride curing agents, amine curing agents, and isocyanate curing agents.
[0008] Preferably, the hydroxysilane-modified GMA acrylic resin is composed of 25wt%-40wt% of epoxy acrylate monomer, 30wt%-60wt% of methacrylate monomer, 1wt%-5wt% of hydroxysilane monomer, 10wt%-25wt% of styrene-based monomer and 1wt%-3wt% of polycarbonate diol monomer with a molecular weight of 1000-2000.
[0009] Preferably, the epoxy acrylate monomer is glycidyl methacrylate, glycidyl acrylate, or an epoxy-containing acrylate monomer.
[0010] Preferably, the methacrylate monomer is specifically methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate and lauryl methacrylate, and an acrylic acid ester having 2 to 11 carbon atoms.
[0011] Preferably, the hydroxysilane monomer in the hydroxysilane-modified GMA acrylic resin is specifically a terminal hydroxyl vinyl silane monomer.
[0012] Preferably, the hydroxysilane-modified GMA acrylic resin has a glass transition temperature of 70° C.-90° C., an epoxy equivalent of 400-500, and a number average molecular weight of 5000-8000.
[0013] A method for preparing a transparent powder coating composition, wherein the synthesis method of a hydroxysilane-modified GMA acrylic resin is prepared by free radical polymerization reaction in the following steps: S1. Add a solvent to a reaction vessel, stir and heat to reflux, mix the terminal hydroxy vinyl silane monomer, glycidyl methacrylate monomer, alkyl methacrylate monomer, styrene monomer and initiator evenly, and add dropwise to the refluxing solvent within 3h-3.5h. After the addition is complete, react under reflux for 2h; S2, continue to slowly drop the remaining mixed solution of initiator and solvent under the condition of solvent reflux, complete the dropwise addition within 10 minutes, and then reflux for 2 hours; S3. After the reflux reaction is completed, polycarbonate diol is added and the solvent is removed by distillation. When the temperature of the reaction system reaches 180°C, a vacuum of -0.09 MPa is applied for 0.5 h, and then the vacuum is released, the material is discharged and cooled to obtain a hydroxysilane-modified GMA acrylic resin.
[0014] Preferably, the transparent powder coating composition is obtained by physically premixing the hydroxysilane-modified GMA acrylic resin, curing agent, leveling agent, degassing agent and polycarbonate diol, and then melt-extruding, tableting, cooling and crushing into fine powder using a twin-screw extruder, and finally passing through a 200-mesh sieve.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention introduces hydroxyl silane monomers into the GMA acrylic resin system of the transparent powder coating for modification. When the coating is cured, the floating of the silane chain segments gives the coating smoothness and scratch resistance, and does not affect the transparency of the coating. The hydroxyl and epoxy functional groups in the acrylic resin are respectively cross-linked with the combination of a carboxyl curing agent and an isocyanate curing agent to increase the curing density and improve the hardness of the coating. Finally, polycarbonate diol is added to the modified acrylic resin adhesive or in the mixing process of the powder coating composition to assist in improving the hardness, wear resistance and boiling resistance adhesion of the coating. The scratch resistance, boiling resistance adhesion and corrosion resistance of the powder coating composition obtained by comprehensive preparation are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 is a list of ingredients of the transparent powder coating composition of the present invention; Figure 2 The present invention is a flow chart of the preparation method of the transparent powder coating composition. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] See also Figure 1 to Figure 2, the present invention provides a technical solution: A transparent powder coating composition comprises the following components by weight: 50wt%-80wt% of a hydroxysilane-modified GMA acrylic resin component, 15wt%-45wt% of a curing agent component, 1%-3% of a polycarbonate diol, 0.1wt%-1.0wt% of a degassing agent, and 0.1wt%-2wt% of a leveling agent.
[0020] The polycarbonate diol is mixed with the hydroxysilane-modified GMA acrylic resin during mixing or premixed in the powder coating composition. It can be mixed with other coating components after being fully mixed in the acrylic resin, or it can be melt mixed with the powder coating composition as a separate component during extrusion. The polycarbonate diol used in the present invention has a molecular weight of 1000-2000 and can be purchased from Asahi Chemical of Japan under the DURANOL brand, such as DURANOL T5652. Adding polycarbonate diol to the powder coating system helps to improve the hardness and friction resistance of the coating and the water boiling adhesion.
[0021] The curing agent that can undergo crosslinking reaction with the hydroxysilane-modified GMA acrylic resin of the present invention can be a compound containing a carboxyl group, an amine group, an isocyanate group, and a combination thereof. The curing agent component containing a carboxyl group is preferably a polycarboxylic acid, such as dodecanedioic acid, and the isocyanate curing agent is preferably a caprolactam-blocked isocyanate, such as K7150 of Lu'an Jietongda New Materials Co., Ltd.
[0022] The hydroxysilane-modified GMA acrylic resin comprises: 25wt%-40wt% of epoxy acrylate monomer, 30wt%-60wt% of methacrylate monomer, 1wt%-5wt% of hydroxysilane monomer, 10wt%-25wt% of styrene monomer and 1wt%-3wt% of polycarbonate diol monomer with a molecular weight of 1000-2000.
[0023] The epoxy acrylate monomer is an epoxy acrylate monomer such as glycidyl methacrylate and glycidyl acrylate, and glycidyl methacrylate is preferred in the present invention.
[0024] The methacrylate monomer may be an acrylate having 2 to 11 carbon atoms, such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate and lauryl methacrylate, for example, methyl methacrylate and ethyl methacrylate.
[0025] In the present invention, no special requirements are made for the hydroxy silane monomer, as long as it is a terminal hydroxy vinyl silane monomer that does not undergo a cross-linking reaction with an acrylate monomer, such as SO001OH (terminal hydroxy vinyl silane) selected from Shenzhen Tianqi New Materials. The silane structure is introduced into the acrylic resin by free radical polymerization to improve the smoothness and scratch resistance of the coating. In addition, the hydroxyl group and the epoxy group work together with the carboxyl group and the isocyanate during the curing and cross-linking process to increase the density of the coating and further improve the scratch resistance of the coating.
[0026] The hydroxysilane-modified GMA acrylic resin has a glass transition temperature of 70° C.-90° C., a number average molecular weight of 5000-8000, and an epoxy equivalent of 400-500. The acrylic resin with a high glass transition temperature helps to increase the hardness of the coating, reduce scratches, and improve corrosion resistance.
[0027] The synthesis method of the hydroxysilane-modified GMA acrylic resin is prepared by free radical polymerization reaction in the following steps: S1. Add a solvent to a reaction vessel, stir and heat to reflux, mix the terminal hydroxy vinyl silane monomer, glycidyl methacrylate monomer, alkyl methacrylate monomer, styrene monomer and initiator evenly, and add dropwise to the refluxing solvent within 3h-3.5h. After the addition is complete, react under reflux for 2h; S2, continue to slowly drop the remaining mixed solution of initiator and solvent under the condition of solvent reflux, complete the dropwise addition within 10 minutes, and then reflux for 2 hours; S3, after the reflux reaction is completed, polycarbonate diol is added, and the solvent is removed by distillation. When the temperature of the reaction system reaches 180° C., a vacuum of -0.09 MPa is applied for 0.5 h, and then the vacuum is released, the material is discharged and cooled, and the hydroxysilane-modified GMA acrylic resin of the present invention is obtained.
[0028] The transparent powder coating composition of the present invention is obtained by physically premixing a hydroxysilane-modified GMA acrylic resin, a curing agent, a leveling agent, a degassing agent and a polycarbonate diol, and then using a twin-screw extruder to melt extrude, sheet, cool and crush into fine powder, and finally pass through a 200-mesh sieve.
[0029] Synthesis example 1 Add 100 parts by weight of xylene to a three-necked flask equipped with a N2 inlet, a stirring device, and a condensing device, and continue to heat and stir until reflux. Add 30 parts by weight of glycidyl methacrylate, 35 parts by weight of methyl methacrylate, 20 parts by weight of styrene, 10 parts by weight of ethyl methacrylate, 3 parts by weight of hydroxyvinylsilane, and a mixed solution of 2 parts by weight of butyl acrylate and 5 parts by weight of benzoyl peroxide dropwise within 3 hours, keep the reflux reaction for 2 hours, and add 0.5 parts by weight of benzoyl peroxide and 10 parts by weight of xylene. React again for 2 hours. After the reaction is completed, cool to 100°C, add 1g of polycarbonate diol, and then perform heating distillation and decompression operations to remove the solvent in the polymer resin to obtain the hydroxysilane-modified acrylic resin 1 of the present invention. The epoxy equivalent of the hydroxysilane-modified acrylic resin 1 is 470, the measured number average molecular weight is 5500, and the glass transition temperature is 65°C.
[0030] Synthesis Examples 2-3 and Comparative Synthesis Example 1 According to the components shown in Table 1 below, hydroxysilane-modified GMA acrylic resins 2-3 and Comparative Synthesis Example 1 were synthesized using the same process as Synthesis Example 1.
[0031] Table 1 The SO001OH in this application adopts hydroxy vinyl silane from Shenzhen Tianqi New Material Technology Co., Ltd.
[0032] The DURANOL T5652 of the present application is a polycarbonate diol produced by Asahi Chemical Industry Co., Ltd. of Japan and has a molecular weight of 2,000.
[0033] Examples 1-5 and Comparative Example 1 Application Examples 1-5 and Comparative Example 1 were physically dry-mixed according to the powder coating components listed in Table 2, and then the powder coating components were melt-mixed, tableted, cooled and crushed into fine powder using a twin-screw extruder. Finally, the mixture was sieved with a 200-mesh screen to obtain the transparent powder coating composition of the present invention.
[0034] Table 2 The K7150 of this application adopts Lu'an Jietongda New Materials Co., Ltd., isocyanate curing agent.
[0035] The DURANOL T5652 of the present application adopts polycarbonate diol produced by Asahi Chemical Industry of Japan, and has a molecular weight of 2000.
[0036] The K7572 of this application adopts Lu'an Jietongda New Materials Co., Ltd., a leveling agent.
[0037] The test method is as follows: each coating composition prepared in Table 2 is sprayed onto the surface of a glass substrate by a high-voltage electrostatic spraying method, and the substrate is baked at 200° C. for 10 minutes to completely cure it.
[0038] Transparency: spray transparent powder coating on a standard transparent thin glass plate and bake to cure, visually compare the transparency of the standard transparent thin glass plate and the coating coated with transparent powder coating under transmitted light and rate them, 1 for poor and 10 for excellent, and the standard transparent thin glass plate is rated 10.
[0039] Film thickness: measured using the German BYK company's A-3430 film thickness meter.
[0040] Leveling performance: Leveling performance is rated according to the leveling effect rating standard board of the US PCI, 1 for poor and 10 for excellent.
[0041] Corrosion resistance: Copper accelerated acetate spray (CASS) test was conducted according to ASTM B368-21 test standard. This test method is used to determine the corrosion resistance of the coating in the corrosive environment generated by CASS. After the test lasted for 168 hours, the test panel was washed and dried, and the corrosion of blisters and edges was checked along the grid lines. The corrosion resistance of the coating was evaluated based on the degree of rust on the panel surface, and the maximum rust range of the grid line was 3.0 mm.
[0042] Scratch resistance: The scratch resistance of the coating is judged according to the pencil hardness test standard GBT6739, 6H is the hardest and 6B is the worst.
[0043] Boiling adhesion: The coating sample prepared by the present invention is placed in boiling water at normal pressure for 2 hours and then rated according to GB / T 9286-2021 Paints and varnishes - Cross-cut test, which is divided into 0-5 grades.
[0044] Table 3 Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A transparent powder coating composition, characterized in that: The invention comprises the following components by weight, including 50wt%-80wt% of a hydroxysilane-modified GMA acrylic resin component, 15wt%-45wt% of a curing agent component, 1%-3% of a polycarbonate diol component, 0.1wt%-1.0wt% of a deaerator component, and 0.1wt%-2wt% of a leveling agent component.
2. A transparent powder coating composition according to claim 1, characterized in that: The molecular weight of the polycarbonate diol is between 1000 and 2000, and the polycarbonate diol is added during the synthesis process of the hydroxysilane-modified GMA acrylic resin and the premixing process of the powder coating composition.
3. A transparent powder coating composition according to claim 2, characterized in that: The curing agent component is a compound that undergoes a cross-linking reaction with the hydroxysilane-modified GMA acrylic resin component, including acid and anhydride curing agents, amine curing agents and isocyanate curing agents.
4. A transparent powder coating composition according to claim 3, characterized in that: The hydroxysilane-modified GMA acrylic resin is composed of 25wt%-40wt% of epoxy acrylate monomer, 30wt%-60wt% of methacrylate monomer, 1wt%-5wt% of hydroxysilane monomer, 10wt%-25wt% of styrene-based monomer and 1wt%-3wt% of polycarbonate diol monomer with a molecular weight of 1000-2000.
5. A transparent powder coating composition according to claim 4, characterized in that: The epoxy acrylate monomer is specifically glycidyl methacrylate, glycidyl acrylate, and epoxy-containing acrylate monomer.
6. A transparent powder coating composition according to claim 5, characterized in that: The methacrylate monomer is specifically methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate and lauryl methacrylate, and an acrylic acid ester having 2 to 11 carbon atoms.
7. A transparent powder coating composition according to claim 6, characterized in that: The hydroxysilane monomer in the hydroxysilane-modified GMA acrylic resin is specifically a terminal hydroxyl vinyl silane monomer.
8. A transparent powder coating composition according to claim 7, characterized in that: The hydroxysilane-modified GMA acrylic resin has a glass transition temperature of 70°C-90°C, an epoxy equivalent of 400-500, and a number average molecular weight of 5000-8000.
9. A method for preparing a transparent powder coating composition according to any one of claims 1 to 8, characterized in that: The synthesis method of the hydroxysilane-modified GMA acrylic resin is prepared by free radical polymerization reaction in the following steps: S1. Add a solvent to a reaction vessel, stir and heat to reflux, mix the terminal hydroxy vinyl silane monomer, glycidyl methacrylate monomer, alkyl methacrylate monomer, styrene monomer and initiator evenly, and add dropwise to the refluxing solvent within 3h-3.5h. After the addition is complete, react under reflux for 2h; S2, continue to slowly drop the remaining mixed solution of initiator and solvent under the condition of solvent reflux, complete the dropwise addition within 10 minutes, and then reflux for 2 hours; S3. After the reflux reaction is completed, polycarbonate diol is added and the solvent is removed by distillation. When the temperature of the reaction system reaches 180°C, a vacuum of -0.09 MPa is applied for 0.5 h, and then the vacuum is released, the material is discharged and cooled to obtain a hydroxysilane-modified GMA acrylic resin.
10. The method for preparing a transparent powder coating composition according to claim 9, characterized in that: A transparent powder coating composition is obtained by physically premixing a hydroxysilane-modified GMA acrylic resin, a curing agent, a leveling agent, a degassing agent and polycarbonate diol, then melt-extruding, tableting, cooling and crushing into fine powder using a twin-screw extruder, and finally passing through a 200-mesh sieve.
Citation Information
Patent Citations
Coating composition and method for forming coating film
CN102292405A
High-adhesive-force transparent powder coating
CN108059897A
Coating composition and method for forming coating film
JP2008013647A
Curable composition and cured product thereof
JP2023142613A
Coating composition and method for forming multilayer coating film
WO2009075392A1
Cited By
High-adhesion alcohol-based powder coating composition and preparation method thereof
CN120329851A